Conceptualizing Customer Trust Formation in TikTok Live Shopping: An IT Affordance Lens - He, Wanxuan; Bahtar, Azlin Zanariah; Karim, Rizuwan Abu (Journal of Ecohumanism, 2024)
In recent years, live shopping has become the mainstream of e-commerce in China. TikTok live shopping real-time video technology and real-time sales explanation sales model, beyond the traditional online shopping single graphic form, has received more online shopping users’ favour. TikTok live shopping can show the appearance and function of the product in an all-around way, and provide customers with more comprehensive information about the product and more intimate sales service. This study conceptualises a model of customer trust formation in the TikTok live shopping experience based on an IT affordance perspective. Dimensions of visibility, meta-voicing, and personalisation are proposed to shape utilitarian and hedonic value perceptions subsequently driving trust. An online survey methodology for empirically testing the framework is discussed along with scale operationalisation procedures. Preliminary results show that visibility significantly enhances utilitarian and hedonic values, which in turn strongly influence customer trust while meta-voicing and personalisation have minimal impact. The research highlights the practical significance of leveraging visibility, hedonic, and utilitarian values to enhance consumer trust on platforms like TikTok while noting the need for future studies to address sample diversity limitations.